How does Self Efficacy of Tuberculosis Patients Correlate with the Implementation of Standard Operational Procedure of Treatment? - Husnul khotimah; Fieka Aulia; Bagus Supriyadi (Indonesian Journal of Global Health Research, 2019)
Tuberculosis (TBC) treatment should be consistently done by patients and be interrupted since it will: 1) have an impact on drug and bacterial resistance, 2) take longer treatment, 3) impact on saturation to patients, and 4) increase the doses of the drug. Given the complexities of the above fact, the present study was designed to uncover the correlation between self-efficacy and the implementation of standard operational procedure of treatment. A total sample of 100 respondents were recruited purposively. The instrument employed in this study was a set of questionnaire. The data were analyzed using Spearman Rank Analysis test. In this study, p-value 0,000<0,05 was obtained. The result of this study indicated that there was a relationship between self-efficacy and the implementation of standard operational procedure of treatment encountered by tuberculosis patients. Patients with pulmonary TBC who had high self-efficacy will be able to implement the standard operational procedure at home, including the ethics of coughing, environmental health, smoking prohibition, personal protective equipment, regular taking medicine and nutrition consumption. These are significant in the treatment and prevention of transmission processes. This study has set as a practical perspective in preventing transmission of Tuberculosis within families and communities. Keywords: Tuberculosis (TBC) treatment should be consistently done by patients and be interrupted since it will: 1) have an impact on drug and bacterial resistance, 2) take longer treatment, 3) impact on saturation to patients, and 4) increase the doses of the drug. Given the complexities of the above fact, the present study was designed to uncover the correlation between self-efficacy and the implementation of standard operational procedure of treatment. A total sample of 100 respondents were recruited purposively. The instrument employed in this study was a set of questionnaire. The data were analyzed using Spearman Rank Analysis test. In this study, p-value 0,000<0,05 was obtained. The result of this study indicated that there was a relationship between self-efficacy and the implementation of standard operational procedure of treatment encountered by tuberculosis patients. Patients with pulmonary TBC who had high self-efficacy will be able to implement the standard operational procedure at home, including the ethics of coughing, environmental health, smoking prohibition, personal protective equipment, regular taking medicine and nutrition consumption. These are significant in the treatment and prevention of transmission processes. This study has set as a practical perspective in preventing transmission of Tuberculosis within families and communities. Keywords: self-efficacy, knowledge level, treatment, tuberculosis patient